A Long-Distance Call? Social Space and Corporation Nouvelle's Places of Production. (2nd October 2019) - Cunha Leal, Joana
Abstract : This article analyses the spatial practices of a collective art project developed by Corporation Nouvelle, a group of modernist artists working in Portugal during the First World War. It investigates its formation and activities, while discussing the relationship between the ultra-peripheral places where these activities were designed, and the transnational-cosmopolitan profile that the group developed. The article revisits some well-known data on Robert Delaunay (1885–1941) and Sonia Delaunay (1885–1979), Amadeo de Souza Cardoso (1887–1918) and Corporation Nouvelle 's operations, resting on two interlocked theoretical determinants: the first questions the way we tend to think about space and place as objectified categories; and the second discusses how in art history the notions of center and periphery tend to operate as geographical locations and to function as discrete categories. The case study of Corporation Nouvelle helps to show that such binary opposition is far from exhausting the ways in which peripheral places are perceived and lived. It is also utilized to argue that geography matters: places of production are not mere locations but social constructs that entail a dialectical relationship between the perceived, the conceived, and the lived.